A case of orbital extra-adrenal paraganglioma in a quarter horse - Tomassini, Letizia; Pettinari, Ilaria; Lepri, Elvio; Gialletti, Rodolfo; Bellezza, Enrico; Leonardi, Leonardo (Brazilian Journal of Veterinary Pathology, 2019)
Paragangliomas are tumors originating from paraganglia cells which represent a considerable constituent of the dispersed neuroendocrine system. Rarely these tumors are found within the orbital region. This report documents a case of primary extra-adrenal paraganglioma in a 15-year-old female quarter horse, diagnosed on the basis of clinical signs, gross anatomopathological, histopathological and immunohistochemical investigations. Clinical diagnostics led to full appreciation of the severe tumor invasiveness and to an informed decision by the owner for euthanasia. Gross inspection confirmed the previous clinical assessments of exophthalmos consequential to pressure from the orbital neoplasia, revealing a mass infiltrating into surrounding tissues. Histopathology and immunohistochemistry allowed for the final diagnosis of paraganglioma. Histology sections showed a partially encapsulated infiltrative mass with multifocal angiotropic growth, and composed of polygonal cells organized in nests, packets, and bundles supported by a fibrovascular stroma. The lobules were lined peripherally by spindle cells. The tumor was highly vascular with blood-filled lacunae and multifocal to coalescing areas of liquefactive necrosis. The polygonal cells were characterized by indistinct borders, lightly eosinophilic cytoplasm with moderate amount of granules, round or oval central nuclei with stippled chromatin (“salt and pepper” appearance) and inconspicuous nucleoli. Immunohistochemistry aided in the diagnostic discrimination of paraganglioma from neuroendocrine carcinoma and in the assessment of tumor differentiation. Orbital paraganglioma holds low likelihood for animal survival, but may have good prognosis when timely addressed.